2016
DOI: 10.1149/2.0061702jes
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrodeposition of Thin Metal Films on Functionalized Dielectric Layer and Hydrogen Gas Sensor

Abstract: Harnessing cathodic hydrogen atom generation, metals such as Pt, Pd, Cu, Au and Ni are directly electrodeposited on functionalized dielectric layers of 6 nm thick silicon oxide formed by thermal oxidation of c-Si substrate. Modifying the oxide layer with functional molecules and Au nanoparticles by simple wet chemistry, we can enhance electrodeposition efficiently and thereby electroplate nanoparticles of Pd and Pt to obtain such thin metal films. In particular, Au nanoparticles on amine-modified silicon oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Not only oxidation at dielectric electrode as the cathode but also reduction of organic reactant occurred as shown by the electroorganic reaction from nitrobenzene to aniline ( Table 2 ). In addition, we could electrodeposit various metals directly on the dielectric electrode as reported in the previous works ( 11 , 13 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Not only oxidation at dielectric electrode as the cathode but also reduction of organic reactant occurred as shown by the electroorganic reaction from nitrobenzene to aniline ( Table 2 ). In addition, we could electrodeposit various metals directly on the dielectric electrode as reported in the previous works ( 11 , 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, there is an unusual approach that deserves attention, i.e., electrochemistry at an insulator thin film ( 7 13 ). Electrochemistry at an insulator, in which few charge carriers are available, is counterintuitive and thereby rarely found in the literature.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Layer-by-layer deposition of Cu film formed at a Pb UPD of -443 mV exhibited higher conformability, and step coverage, and (111) texture. The results of this study suggested that the EC-ALD can used for fabricating Cu interconnects [72].…”
Section: Current Status Of Ec-aldmentioning
confidence: 72%